PERANCANGAN SISTEM MONITORING FREKUENSI GELOMBANG RADIO DALAM MENDUKUNG TUGAS POS ANGKATAN LAUT BERBASIS MIKROKONTROLER DAN RTL - SDR - Hernanto Ivan Bahri; Risang Sadewa; Darimanto (AKADEMI ANGKATAN LAUT, 2021)
Violation of Indonesia’s maritime borders by foreign vessels without permission isincreasing, resulting in various losses. Keeping up with the times where increasinglysophisticated technology also helps in the development of military equipment. Tominimize the occurrence of such violations, the radio wave frequency monitoring systemequipment has the feature of being able to monitor radio waves that work at a frequencyof 100 Khz to 1.8 Ghz with the aim of obtaining information to support and increaseawareness in border areas. translated by RTL-SDR and displayed on the display onthe laptop. The selected frequency will be locked and listen to the information carriedby the radio waves using a headset. In addition, as an indicator that this tool is able towork using the Arduino nano microcontroller as a liaison between the Arduino softwareand the hardware used as an indicator that this tool is ready to operate. Microcontrollerbased radio wave frequency monitoring systems and RTL-SDR can be used to assistthe task of the Navy post in improving security and reducing the risk of violations in theIndonesian maritime border area. The most frequent violations are foreign ships thatoften enter the Indonesian sea border area without permission. From the results of theanalysis and testing of the tool that this tool is very effective in supporting the task ofthe Navy post in guarding Indonesia’s maritime borders. This design will be better if itis added with a foreign language translator feature to make it easier for operators toprocess the information obtained.